Integrated development strategy of the catchment area of the Tisza river - Cocean, Pompei; Pop, Ana-Maria; Papp, Lelia (Acta Agraria Debreceniensis, 2014)
The main challenge for mankind has always been to eliminate the borders of its living space, as well as to explore and discover its new faces. Contemporary literature strengthens this postulate. It is the preference of the experts of various fields in spatial analysis is to consider space to be repairable, changeable and organisable. In accordance with this axiom, the five affected countries in the catchment area of the Tisza river (Hungary, Romania, Ukraine, Slovakia and Serbia) worked out an integrated, mutual standpoint to support the problems of the catchment area and to exploit its opportunities with the aim to support transnational cooperation. They laid great emphasis on the existing resources which could become the driving force behind regional development directions. This study contains the summarised outcomes of the TICAD project (SEE/A 638/4.2./X) which was drawn up as a result of cooperation between renowned institutions of the five affected countries within the South East Europe Transnational Cooperation Programme (lead partner: VÁTI, Hungary).